Influence of different playing surfaces on bone mass accretion in male adolescent football players: A one-season study - Lozano-Berges, G.; Matute-Llorente, Á.; Gómez-Bruton, A.; González-Agüero, A.; Vicente-Rodriguez, G.; Casajús, J. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
There are different surfaces on which football is played, but their influence on bone mass accretion still remains unknown. The aims of this study were to compare bone mass accretion between football players and controls, and evaluate the influence of two different playing surfaces on bone accretion. A total of 27 male football players (13.2 ± 0.5 years) and 15 controls (12.6 ± 1.1 years) participated in this study. Football players were classified into two groups according to the surface they trained on: 14 on third-generation artificial turf with elastic layer and 13 on third-generation artificial turf without elastic layer. Bone mineral content and areal bone mineral density were measured using dual-energy X-ray absorptiometry. Bone mineral apparent density variables were calculated. Bone geometry and strength of the non-dominant tibia were assessed with peripheral quantitative computed tomography. For both football players and controls, bone variables measured at subtotal body, lumbar spine, legs and tibia (p < 0.05) significantly increased. Based on the time spent practicing football, the increase in areal bone mineral density for the legs (p < 0.05) was higher in football players than controls. Moreover, lumbar spine bone mineral apparent density increased more in third-generation artificial turf without elastic layer players in comparison with third-generation artificial turf with elastic layer players (p < 0.05). Playing football on third-generation artificial turf with elastic layer and third-generation artificial turf without elastic layer seems to positively affect bone mass during growth. After playing for one season on these playing surfaces, football practice on third-generation artificial turf without elastic layer with the lower shock absorption seems to have produced the highest increment in areal bone mineral density at lumbar spine. Thus, football practice on surfaces with lower shock absorption could provide an extra benefit on bone health.